OVERLAP OF KAROO AND FERRAR MAGMA TYPES IN KWAZULU-NATAL, SOUTH AFRICA - Riley T.R.; Curtis M.L.; Leat P.T.; Watkeys M.K.; Duncan R.A.; Millar I.L.; Owens W.H. (My University, 2006)
A suite of mafic dykes from the Underberg region of southern KwaZulu-Natal (South Africa) were intruded at ?178?Ma, coincident in age with the major Okavango Dyke Swarm of Botswana, and also coincident with minor Karoo-related intrusions of the northern and central Lebombo. The dykes are all low-Ti–Zr tholeiites, they trend NW–SE and are presumed to continue into the Karoo central area of the Lesotho Highlands. In many respects, the Underberg dykes are similar to the majority of the low-Ti–Zr volcanic and subvolcanic intrusions of the Karoo; however, their 87Sr/86Sr and ɛNd isotope ratios are either ‘Ferrar-like’ (87Sr/86Sr ?0·710; ɛNd < ?3) or transitional between Karoo low-Ti–Zr and Ferrar low-Ti magmas. A potential Ferrar source for at least some of the Underberg dykes is supported by anisotropy of magnetic susceptibility analyses of the dyke suite, which demonstrate absolute flow direction from the SE to the NW, consistent with Gondwana reconstructions. The role of crustal contamination and combined fractional crystallization is also demonstrated to have played a key role in the petrogenesis of the Underberg dykes, involving a local upper crust contaminant. However, the composition of the ‘Ferrar-like’ dykes cannot be easily explained by AFC processes, but they do demonstrate that melting of a lithospheric mantle source enriched to a small degree by subduction-derived fluid was also important.
Keywords: dyke; basalt; crustal contamination; large igneous province